Misconception Analysis of Student Books on the Theme of Building Household - Fuadi, Muhammad; Susilo, Mohamad Joko (The Indonesian Institute of Science and Technology Research, 2023)
This study aimed to discover whether there were misconceptions about Islamic religious education learning materials and manners regarding the theme of the beauty of household mahligai to students. This type of research is a qualitative literature review with a naturalistic approach. In this case, the researcher examines books, journals, theses, and other sources that discuss textbooks on Islamic religious education and morals and the book of Qurrotul Uyun. The data collection technique used in this is a documentary literature review with the object of discussion in question. Data in the library is processed by editing, organising, and finding. Researchers used content analysis in this study. Based on the results of the study, it was found that the misconceptions in the PAI and Characteristics books for grade 12 were related to students, teachers, textbooks, context, and methods. Suppose the categories of misconceptions are sorted from largest to smallest. In that case, they are found in PAI books and manners for class 12, namely oversimplifications, misidentifications, over generalisations, under generalisations and obsolete concepts and terms. None of the textbook’s analytical material is free from misconceptions.